Membrane Disruption and Enhanced Inhibition of Cell‐Wall Biosynthesis: A Synergistic Approach to Tackle Vancomycin‐Resistant Bacteria. Issue 46 (16th October 2015) - Yarlagadda, Venkateswarlu; Samaddar, Sandip; Paramanandham, Krishnamoorthy; Shome, Bibek R.; Haldar, Jayanta
Abstract: Resistance to glycopeptide antibiotics, the drugs of choice for life‐threatening bacterial infections, is on the rise. In order to counter the threat of glycopeptide‐resistant bacteria, we report development of a new class of semi‐synthetic glycopeptide antibiotics, which not only target the bacterial membrane but also display enhanced inhibition of cell‐wall biosynthesis through increased binding affinity to their target peptides. The combined effect of these two mechanisms resulted in improved in vitro activity of two to three orders of magnitude over vancomycin and no propensity to trigger drug resistance in bacteria. In murine model of kidney infection, the optimized compound was able to bring bacterial burden down by about 6 logs at 12 mg kg −1 with no observed toxicity. The results furnished in this report emphasize the potential of this class of compounds as future antibiotics for drug‐resistant Gram‐positive infections. Abstract : Glycopeptide antibiotics : Newly developed glycopeptide antibiotics demonstrated high activity against multidrug‐resistant bacteria and showed the ability to stall bacterial resistance development because of incorporation of a novel membrane‐disrupting mechanism and enhanced inhibition of the cell‐wall synthesis. The results emphasize that this multipronged approach could be used clinically to develop the next generation of glycopeptide antibiotics.